2020
DOI: 10.1016/j.ejvs.2020.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Non-operative Management in Asymptomatic Patients with 70%–80% Internal Carotid Artery Stenosis by Duplex Criteria

Abstract: WHAT THIS PAPER ADDSIn this single institution retrospective analysis of patients with asymptomatic internal carotid artery stenosis identified on duplex ultrasound as moderate to severe (70%e80%) from 2003 to 2018. There was a low rate (5.3%) of stroke/transient ischaemic attack without documented progression of stenosis, but there was a high rate (24.1%) of stenosis progression, as well as a 16.3% mortality rate at five years. The data reinforce the need to follow these patients closely, and patients at a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
(27 reference statements)
0
3
0
2
Order By: Relevance
“…After screening of 5915 unique reports and assessing the full texts of 231 for eligibility, we included 73 studies reporting 28 625 patients with ≥50% ACAS (Figure 1; Table S2). 8–10,16–85…”
Section: Resultsmentioning
confidence: 99%
“…After screening of 5915 unique reports and assessing the full texts of 231 for eligibility, we included 73 studies reporting 28 625 patients with ≥50% ACAS (Figure 1; Table S2). 8–10,16–85…”
Section: Resultsmentioning
confidence: 99%
“…En los últimos 10 años, se han llevado a cabo estudios que han permitido conocer la historia natural de la enfermedad del paciente con aterosclerosis y estenosis carotídea asintomática, manejados con tratamiento médico (37)(38)(39)(40)(41) . Cheng et al (37) realizaron un análisis retrospectivo de 206 carótidas con estenosis asintomática del 70 %-80 %, donde se observó que, durante una ventana de tiempo de 15 años, aproximadamente, se encontró progresión en el 24 % de estas, y que hubo una incidencia de ictus del 5,3 %. Dentro de los factores de riesgo reportados para el ictus sin progresión 33).…”
Section: Evidencia Sobre Desenlaces En El Manejo Médico De La Aterosc...unclassified
“…Dentro de los factores de riesgo reportados para el ictus sin progresión 33). Por tanto, los autores de este estudio concluyeron que se evidenció una alta frecuencia de progresión de estenosis, pero baja en ictus (37) .…”
Section: Evidencia Sobre Desenlaces En El Manejo Médico De La Aterosc...unclassified
“…In terms of the natural history of asymptomatic higher grade, i.e., >70% stenosis, Cheng et al . [ 74 ] reported that the 5-year risk of stroke or TIA associated with ipsilateral stenosis was 5.3%. This study was based upon serial carotid duplex scan with a progression rate of stenosis, over time, of 24.1%.…”
Section: Assessment and Treatment Of Stroke Risk With Asymptomatic Ca...mentioning
confidence: 99%